TECHNICAL DRAMATIC TECHNIQUES IN SELECT PLAYS OF VIJAY TENDULKAR - P. Rajeswari; M. P. Ganesan (International Journal of Research -GRANTHAALAYAH, 2026)
This paper is to study the techniques of dramatic techniques employed in Vijay Tendulkar’s plays which analyze the raw realities of our society, focusing on reflecting human cruelty, social hypocrisy, and power dynamics. Vijay Tendulkar has used innovative dramatic techniques like play- within _a – play, deviation from the three-act structure which has broken the conventional structure to create a dynamic and realistic theatrical experience. His usage of authentic simple language which helps to explore deeply complex human emotions makes the audience feel genuine and relatable. Revelation of psychological depth through the dialogue which exposes their inner thoughts, hypocrisy and frustrations is a popular technique of Vijay Tendulkar. Another technique is dramatic technique is his usage of powerful Symbolism and imagery. Allegory and myth, symbolic setting and props which brings out psychological and physical violence. Postmodern and realistic elements helps to voice for the marginalized groups and lashes court hypocrisy and judgement against truth. The study also highlights how he utilizes silence, pauses and fragmented dialogues as dramatic tools to deepen psychological tension and expose hidden conflicts. These techniques are highlighted in his plays such as Gashiram Kotwal and Silence! The Court is in Session, Sakharam Binder. Tendulkar’s dramatic approach involves bold experimentation with structure, characterization, and staging. Notably, in “Ghashiram Kotwal”, he incorporates the Marati folk form Tamasha, integrates chorus and multiple Sheroles for the sutradhar, and applies symbolic uses of songs, dance, masks, and mime to create a universal impact while presenting local stories.